Anticipated reduction in COVID-19 mortality due to population-wide BCG vaccination: evidence from Germany - Daniela Marín-Hernández; Douglas F. Nixon; Nathaniel Hupert (Taylor & Francis Group, 2021)
Bacillus Calmette-Guérin (BCG) vaccine is known to have "bystander benefits" in protecting against heterologous infections; interim analysis of the "ACTIVATE" trial shows protection against respiratory infections in the elderly population. Epidemiologic studies suggest a potential benefit of BCG vaccination on COVID-19 outcomes. Differential past BCG vaccination policies between the former East and West German states provides a unique natural experiment to assess the potential effect of prior BCG vaccination on COVID-19. We estimated a 5% heterologous vaccine efficacy in the highly vaccinated former East Germany using the COVID-19 International Modeling (CoMo) Consortium model. A comparable BCG vaccination campaign undertaken prior to the pandemic in former West Germany, instituted along with known country-wide transmission reduction measures, is associated with a 37% decrease in projected mortality by mid-summer, 2020. These findings support a combined heterologous vaccine and non-pharmaceutical interventions (HVI+NPI) approach to mitigate the SARS-CoV-2 pandemic until SARS-CoV-2 specific vaccines are widely distributed.